Towards research practice at the School of Languages. An alternative - Montoya, Paula Andrea (Íkala, Revista de Lenguaje y Cultura, 2003)
This article expounds a proposal for a research practice in the School of Languages at the Universidad de Antioquia, carried out by the Translatology Research Group. The purpose of this proposal is that students and lecturers commit themselves to research, which is the fundamental aim of the School of Languages. This research aims to improve the quality of education, and with their work as professional translators, encourages them to reflect on theory, methodology and evaluation. Received: 19-06-03 / Accepted: 28-08-03 How to reference this article: Montoya, P. A. (2003). Por una práctica investigativa en la Escuela de Idiomas: una alternativa. Íkala. 8(1), pp. 239 – 247